Revisiting the molecular landscape of Rosai-Dorfman disease: insights from whole exome sequencing of Saudi patients - Binhassan, Sarah; Samman, Manar; Al-Sheikh, Yazeed; Alshakweer, Wafaa; Alhalouli, Tahani; Alshamlan, Najd; Abudawood, Manal (Frontiers in Oncology, 2025)
Rosai-Dorfman disease (RDD) has traditionally been viewed as a reactive histiocytic disorder, defined by its unique clinical features and immunophenotype. However, recent genetic studies suggest a more complex molecular landscape, challenging the notion of RDD as solely reactive and hinting at a possible neoplastic component. Mutations in MAPK/ERK pathway genes, such as KRAS and MAP2K1, have been observed in up to 33% of cases. Additional genetic alterations in cell cycle regulation, DNA repair, and other processes, along with low-frequency BRAF mutations, further emphasize this complexity. To better understand the molecular basis of RDD and enhance diagnostic precision, we conducted whole exome sequencing (WES) on seven Saudi patients with RDD, comparing their genetic profiles with existing literature. While no kinase driver mutations were detected, our analysis revealed thirteen distinct mutations. Recurrent mutations were observed in CD207 and TDG, each found in six patients. CD207 is linked to antigen processing, while TDG is associated with DNA repair. MUC4 and PDS5A mutations, related to cell cycle regulation, were each identified in three patients. DNMT3A mutation, affecting DNA methylation, was found in two patients. Single mutations were observed in BRCA1, LATS2, ATM, USP35, and CIC, associated with DNA repair, the ubiquitin proteasome pathway, and transcriptional regulation respectively. These findings offer insights into the genetic makeup of RDD, revealing candidate genes and expanding our understanding of the disease’s molecular complexities. By uncovering these genetic markers, this study contributes to the ongoing efforts to develop more accurate diagnostic tools and refine the classification of RDD, paving the way for improved patient care and disease management.